2020
DOI: 10.5334/tohm.565
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolic Changes with Longitudinal Transcutaneous Afferent Patterned Stimulation in Essential Tremor Subjects

Abstract: Background: Non-invasive peripheral nerve stimulation, also referred to as transcutaneous afferent patterned stimulation (TAPS), reduces hand tremor in essential tremor (ET) subjects. However, the mechanism of action of TAPS is unknown. Here, we investigated changes in brain metabolism over three months of TAPS use in ET subjects. Methods: This was an interventional, open label, single group study enrolling 5 ET subjects. They received 40 minutes of TAPS treatment twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…24,[43][44][45] Pharmacotherapy is currently the mainstay for ET treatment. 13,14,46 However, it has been reported that the first-line agents are ineffective in 30% to 70% of patients due to lack of response, adverse effects, and poor adherence and persistence. 11,[13][14][15]46 Our data show the wide spectrum of comorbidities among patients with ET, supporting the need for noninvasive, nonpharmacological treatments to minimize risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,[43][44][45] Pharmacotherapy is currently the mainstay for ET treatment. 13,14,46 However, it has been reported that the first-line agents are ineffective in 30% to 70% of patients due to lack of response, adverse effects, and poor adherence and persistence. 11,[13][14][15]46 Our data show the wide spectrum of comorbidities among patients with ET, supporting the need for noninvasive, nonpharmacological treatments to minimize risk of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,46 However, it has been reported that the first-line agents are ineffective in 30% to 70% of patients due to lack of response, adverse effects, and poor adherence and persistence. 11,[13][14][15]46 Our data show the wide spectrum of comorbidities among patients with ET, supporting the need for noninvasive, nonpharmacological treatments to minimize risk of adverse events. Novel treatment options can empower healthcare providers and ET care teams to provide safe and effective therapies that can be tailored to the specific healthcare needs of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…TAPS doses consist of forty minutes of noninvasive stimulation that alternates between the median and radial nerves at the wrist at a patient's tremor frequency; motion sensors on a wrist-worn TAPS delivery device measure this tremor frequency during an initial calibration [54]. Randomized sham-controlled single-session clinical trials and subsequent longitudinal at-home clinical trials in ET have shown that TAPS therapy provides at least 50% lasting tremor reduction for the majority of patients, with over 90% of patients receiving at least some tremor reduction [53][54][55][56][57]; that tremor reduction with TAPS persists for over an hour after a TAPS dose for many patients [54,56]; and that repeated daily use of TAPS therapy over three months indicated no habituation or dose tolerance-induced loss of tremor reduction [54]. Efficacy of TAPS for tremor reduction was similar between patients on and off tremor medication [54].…”
Section: Clinically Available Tremor Management Pes Therapiesmentioning
confidence: 99%
“…One hypothesis for this lasting effect is that calibrated afferent PES (TAPS) produces a dephasing effect in the thalamus similar to the coordinated reset by DBS [104,105]. Another hypothesis is that afferent PES has a lasting effect on cerebellar circuits that project into the thalamo-cortical network, as supported by the metabolic increase in the cerebellar region measured via Single Photon Emission Computed Tomography (SPECT) imaging after three months of TAPS therapy in 5 ET patients [57]. Purkinje cell degeneration at the cerebellum is one of the main hypotheses for the cause of ET [106] and the cerebellum is involved in motor control and learning by integrating projections from the thalamo-cortical circuit and primary afferents to adjust the motor response.…”
Section: Supraspinal Modulationmentioning
confidence: 99%
“…TAPS therapy consists of stimulation of the median and radial nerves at the wrist at a frequency individualized to each patient's tremor [17]. TAPS is hypothesized to control ET symptoms by dephasing neural oscillations at the Ventral Intermediate (VIM) nucleus, the thalamic relay where deep brain stimulation (DBS) is implanted for the treatment of ET [18][19][20][21]. In a randomized single-session clinical trial, the magnitude of improvement across tasks in the treatment group corresponded to a 49% reduction in tremor according to patient's self-rated quality of life as measured by Bain and Findley Activities of Daily Living (BF-ADL) and a 42% reduction according to physician-rated Tremor Research Group Essential Tremor Rating Scale (TETRAS) [17].…”
Section: Introductionmentioning
confidence: 99%